2014
DOI: 10.9775/kvfd.2014.11425
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Salmonella from Layer Flocks and Typing of the Isolates

Abstract: ÖzetÇalışmada, farklı yetiştirme dönemlerindeki yumurtacı tavuklarda Salmonella aranmasında farklı metotların değerlendirilmesi, elde edilen izolatların serotiplendirilmesi, ribotiplendirilmesi ve antibiyotiplendirilmesi ile Salmonella yaygınlığının belirlenmesi amaçlandı. Bu amaçla, 58 adet ticari yumurtacı tavuk kümesinden yetiştirmenin 15., 25. ve 40. haftalık dönemlerinde alınan toplam 174 adet drag svap örneği, Salmonella varlığı açısından standart kültür metodu olan ISO (ISO 6579:2002/Amd 1:2007 -ISO) ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Many studies have been conducted to reveal the presence and distribution of Salmonella species in chicken, worldwide and the prevalence rates ranging from 4 to 92% have been reported [24,25]. On the other hand, field and abattoir based studies carried out different regions of Turkey have declared the proportions ranging from 0.4 to 39% [8][9][10]. In the analysis of sock swabs and internal organ samples collected from the total of 77 chicken flocks in the present study, Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have been conducted to reveal the presence and distribution of Salmonella species in chicken, worldwide and the prevalence rates ranging from 4 to 92% have been reported [24,25]. On the other hand, field and abattoir based studies carried out different regions of Turkey have declared the proportions ranging from 0.4 to 39% [8][9][10]. In the analysis of sock swabs and internal organ samples collected from the total of 77 chicken flocks in the present study, Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Also, according to 2016 EFSA report, S. Infantis (37%) was the most commonly reported Salmonella serotype in broiler flocks, followed by S. Enteritidis (14%) [34]. In Turkey, previous studies based on conventional serotyping reported varied results in terms of the frequency of Salmonella agents depending on the study region and sample type but, overall evaluation of these studies showed that most commonly identified serotypes in chicken flocks were S. Enteritidis, S. Typhimurium and S. Infantis [9,10,26,[35][36][37][38][39]. In the present study, mPCR analysis of Salmonella sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The elevated presence of this serotype in chicken products agrees with S. Enteritidis being the predominant serotype associated with outbreaks due the consumption of eggs [6] . Accordingly, S. Enteritidis, S. Typhimurium, S. Paratyphi B and S. Typhi are the most common serotypes isolated from humans [14] and poultry [27] in Turkey.…”
Section: As Shownmentioning
confidence: 99%